Pemulihan Dan Penguatan Manajemen Usaha Pasca Pandemic Covid-19 Pada Usaha Batik Mikro Di Kecamatan Kalibagor - Sri Lestari; Najmudin Najmudin; Devani Laksmi Indyastuti (FKIP, Universitas Palangka Raya, 2023)
The target audience for this Science and Technology Application Program is the Nurimas batik making group which has 11 members and is located in Pajerukan Village, Kalibagor District. The emergence of this group was triggered by the large demand for batik products in Kalibagor District in particular and in Banyumas Regency in general which has not been served, namely 10,020 people from school students, teachers and employees within the Kalibagor District. School students, teachers and employees in Banyumas Regency are generally required to wear batik clothing 2-3 days a week. Meanwhile, the Nurimas Batik group is the only batik craftsman from the Kalibagor District area. The partners' main problems are that many of the production equipment is no longer suitable and there is a lack of capital due to the Covid 19 pandemic, the partners have not started a business in promoting their products to potential customers, the partners have not mastered the online marketing or sales of their batik, the partners do not understand group management. which is good, the partners do not implement order in their group's administrative records, the batik motif designs of the batik-making partners are still simple and not yet varied, their mastery of business management is still lacking and they do not carry out standardized bookkeeping. This activity has resulted in an increase in equipment and production materials owned by partners, increased sales, the ability to market on-line, increased partner mastery of group management and administration, results of administering activities, group financial reports, and scientific articles. In order to obtain the specified goals and outcomes, the team carries out outreach programs to partners, practice and mentoring. The method used to evaluate is to compare the level of knowledge with capabilities and production results. Then compare marketing activities before the Science and Technology Application service program and after.